REASSURED Test System for Food Control—Preparation of LAMP Reaction Mixtures for In-Field Identification of Plant and Animal Species - Nathalie Holz; Nils Wax; Marie Oest; Markus Fischer (Applied Sciences)
The potential of loop-mediated isothermal amplification (LAMP) assays for species identification in medical diagnostics, food safety, and authentication is indisputable. The challenge in commercialization of such DNA-based rapid test methods for resource-limited settings is the on-site availability of the required reagents and an intuitive read-out system. In this work, reaction mixtures for LAMP assays for the detection of animal (plaice) and plant food (safflower) were lyophilized and stored at room temperature for up to 24 weeks, demonstrating that refrigeration of reagents after lyophilization is not absolutely necessary. During this period, reaction mixtures were stable and the polymerase showed no loss of activity. In addition, mobile testing, including DNA isolation, using the lyophilized LAMP reaction mixtures and a handheld fluorescence detection read-out system (Doctor Vida Pocket test) was successfully performed outside of the laboratory environment in less than 40 min using a proposed standard operation procedure. The results highlight that the use of the lyophilized LAMP reaction for food control purposes has the potential to meet the WHO-proposed REASSURED criteria.